(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: The number of menopausal women who suffer from low level estrogen-associated type-2 diabetes has been increasing recently. The role of estrogen in metabolism of glucose depends on estrogen receptor alpha expression that is regulated by estrogen receptor alpha gene (ESR ?). PvuII and XbaI polymorphisms in the ESR ? receptor may decrease the expression of ESR ? protein and receptor activity, thereby increasing the risk of developing type 2 diabetes mellitus in menopausal women. Purpose: to determine the ESR ? polymorphism as a risk factor for type 2 diabetes mellitus (DM) in menopause women of Javanese in Indonesia. Methods: Sixty five menopausal women were recruited for the study consisted of 40 women with T2DM and 25 women as control. PvuII and XbaI polymorphisms were determined by polymerase chain reacton-restriction fragment length polymorphism (PCR-RFLP). The absence of PvuII and XbaI restriction sites were indicated by P1 and X1 and presence by P2 and X2, respectively. Chai Square test were used in statistical analyisis to measure Hardy Weinberg Equilibrium (HWE) and the risk of P1/P2 and X1/X2 allele for suffering T2DM. Results: PvuII genotype was distributed as; 22.5% (P1P1), 45% (P1P2), 32.5% (P2P2) while XbaI genotype was distributed as 10 % (X1X1), 62.5% (X1X2) and 27.5% (X2X2) in diabetics respectively. There was no difference in distribution of P1 and P2 between diabetics and non diabetics but difference for X1 and X2 existed between groups. The frequency of P2 allele was 55 % while P1 allele frequency is 45% in diabetics. X2 allele frequency was 58.8% while X1 allele is 41.2%. X2 allele had an impact on the 3.6 times higher risk of getting type 2 diabetes in Javanese menopausal women (OR = 3.662, CI = 1.711 to 7.840). Conclusions: PvuII and XbaI polymorphism was found in Javanese menopause women of Indonesia in patients with type 2 diabetes mellitus. The allele frequency of P2 and X2 are 55% and 58.8% respectively. X2 allele was found as a risk factor for type 2 diabetes mellitus in Javanese menopause women of Indonesia. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 171-179 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14946